Science and technology in catalysis, 1998 : proceedings of the third Tokyo Conference on Advanced Catalytic Science and Technology, Tokyo, July 19-24, 1998 - Hattori, Hideshi; Otsuki, Kiyoshi (Studies in surface science and catalysis ;, 1999)
In 1990, the Catalysis Society of Japan embarked on a new series of international conferences aiming to promote closer cooperation between technology and fundamental research and create new concepts for the development of useful catalytic systems. This series of conferences is named Tokyo Conference on Advanced Catalytic Science and Technology (TOCAT). The success of TOCAT 1 in 1990 and the second conference in 1994 encouraged the Society to hold the third conference, TOCAT 3, following the same idea and style as the previous conferences. The present proceedings contain 87 papers: 5 plenary lectures, 10 invited papers, 34 papers selected for oral presentation, and 38 papers presented in the industrial poster session. The submitted manuscripts were peer-reviewed by experts in the field.